A Review of Research on Perceived Employability and Its Consequences - Sakaki, Jeff (International Journal of Accounting and Financial Reporting, 2022)
Perceived employability is an individual’s subjective perception of the possibility of obtaining and maintaining (current or future) employment, which has gradually become an important personal resource to help employees adapt to the uncertain workplace environment. From the perspective of enterprises, high employability awareness may stimulate high job turnover of employees, which leads enterprises into the risk of training and development costs being wasted. This paper first reviews the connotation, structure and measurement of perceived employability, and then systematically sorts out the effects and mechanisms of perceived employability from the perspectives of career management, occupational health psychology and organizational behavior, so as to clarify the internal reasons for the differentiated effects of perceived employability on individuals and enterprises to a certain extent.